Pengaruh Kualitas Pelayanan Bank Syariah Terhadap Kepuasan Mahasiswa Sebagai Nasabah Bank Syariah - Muhammad al-‘Ayzar; Tria Okta Ameliah; Muhamad Nouval Azmi; Wahyu Hidayat; Zaini Ibrahim (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Islamic banks, as the name implies, are banks based on Islamic law (sharia) which do not run an interest system in their operations because this is considered a ribawi mechanism. In carrying out its operations, Islamic banks take profits by using a profit-sharing system. The operational activities of Islamic banks do not only focus on raising and channeling funds, but service quality is also an important factor in maximizing profits. The purpose of this study is to determine whether the quality of Islamic bank services has an influence on student satisfaction as Islamic bank customers. And this research consists of two variables, namely service quality and customer satisfaction. This research method uses quantitative methods with regression tests given to 40 respondents with 10 questions.